People LGBT+ homeless: a review of related literature - Rodríguez Pérez, José Gabriel (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Introduction: Lesbian, gay, bisexual, transgender and other identities (LGBT+) people are invisible despite being overrepresented in the homeless population in many countries. Methodology: Systematic review of the literature between February and April 2022 on LGBT+ PSH studies, published in Scopus and Google Scholar. All articles were assessed for eligibility and data extracted. Results: A total of 51 articles were selected and a table summarizing their characteristics was created. Conclusions: it is necessary to increase research, expand the LGBT+ sample to achieve better intervention/prevention of homelessness among these people.